2015
DOI: 10.1055/s-0034-1396260
|View full text |Cite
|
Sign up to set email alerts
|

Prävention von Fahrradfahrerunfällen

Abstract: For a very precise analysis of all injured bicyclists in Germany it would be important to have definitions for "severely injured", "seriously injured" and "critically injured". By this, e.g., two-thirds of surgically treated bicyclists who are not registered by the police could become available for a general analysis. Elderly bicyclists (> 60 years) are a minority (10 %) but represent a majority (50 %) of all fatalities. They profit most by wearing a helmet and would be less injured by using special bicycle ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…The majority of bicycle accidents occur in road traffic: cyclists collide with cars, other cyclists, or pedestrians (16, 30, 31). Our investigation showed that fractures usually occur during collisions with a car, an object (also a fall), or another cyclist.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bicycle accidents occur in road traffic: cyclists collide with cars, other cyclists, or pedestrians (16, 30, 31). Our investigation showed that fractures usually occur during collisions with a car, an object (also a fall), or another cyclist.…”
Section: Discussionmentioning
confidence: 99%
“…Seit Erhebung der Daten haben die Verkaufszahlen von Fahrrädern und E-Bikes drastisch zugenommen, und es kam zu einer Vielzahl von Verkehrsprojekten, um die Sicherheit von Fahrradfahrern zu erhöhen [12]. Ferner ist die Zahl der am In Deutschland wird die Tragefrequenz von Fahrradhelmen über alle Altersgruppen zwischen 4,1 und 14% beziffert [14,28,29]. Mit steigendem Alter nimmt das Reaktionsvermögen schrittweise ab [5], und es wäre prinzipiell denkbar, dass es hierdurch bei einem Sturz häufiger zu einem Kopfanprall kommt.…”
Section: Diskussionunclassified
“…Oft tragen auch Mängel in der Ausgestaltung von Knotenpunkten zum Unfallgeschehen bei. So stellen sich gerade bei den Abbiegeunfällen mit Radfahrer-oder Fußgängerbeteiligung besonders oft Beeinträchtigungen der Sicht zwischen den Verkehrsteilnehmenden als problematisch heraus [15]. Weitere Faktoren, wie z.…”
Section: Hintergrundunclassified
“…Loidl et al [18] fassen für ihre Fallstudie aus Österreich einige wesentliche methodische Anforderungen an die Auswertung von Verkehrsunfällen mit Radfahrerbeteiligung zusammen und zeigen Potenziale der räumlich-zeitlichen Datenexploration auf. Solche Studien können eine Grundlage für die verstärkt geforderten evidenzbasierten Ansätze zur Sicherheit bei der aktiven Mobilität darstellen, um wirksame Maßnahmen zu identifizieren und unangemessene zu vermeiden [15,19].…”
Section: Hintergrundunclassified